2015
DOI: 10.1007/s00253-015-6962-x
|View full text |Cite
|
Sign up to set email alerts
|

A live attenuated BCG vaccine overexpressing multistage antigens Ag85B and HspX provides superior protection against Mycobacterium tuberculosis infection

Abstract: Tuberculosis (TB) remains one of the most menacing infectious diseases, although attenuated Mycobacterium bovis Bacillus Calmette-Guerin (BCG) vaccine has been widely used to protect children against primary TB. There are increasing evidences that rapid growing and dormant Mycobacterium tuberculosis (M. tuberculosis) coexist in vivo after infection. However, BCG vaccine only elicits cell-mediated immune responses to secretory antigens expressed by rapid growing pathogen. BCG vaccine is thus unable to thwart th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Several studies have shown that BCG induces polyfunctional mycobacteria-specific CD4 + T cells detected among lung (9, 38) and splenic (9, 3944) lymphocyte populations (Table 1). Darrah et al found that polyfunctional mycobacterial CD4 + T cells produced more cytokine on a per cell basis than do those producing two or one cytokines, similar to Leishmania -specific polyfunctional CD4 + T cells (9).…”
Section: Tb Vaccines Induce Polyfunctional T Cells In Animal Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that BCG induces polyfunctional mycobacteria-specific CD4 + T cells detected among lung (9, 38) and splenic (9, 3944) lymphocyte populations (Table 1). Darrah et al found that polyfunctional mycobacterial CD4 + T cells produced more cytokine on a per cell basis than do those producing two or one cytokines, similar to Leishmania -specific polyfunctional CD4 + T cells (9).…”
Section: Tb Vaccines Induce Polyfunctional T Cells In Animal Modelsmentioning
confidence: 99%
“…Darrah et al found that polyfunctional mycobacterial CD4 + T cells produced more cytokine on a per cell basis than do those producing two or one cytokines, similar to Leishmania -specific polyfunctional CD4 + T cells (9). In the murine TB model, these T cell responses constitute minor (38, 39, 42, 44), predominant (43), or major (9) subsets within the first 2–4 months after immunization. In addition, polyfunctional CD4 + T cells have been detected among CD44 + memory T cell populations as early as 3 weeks after vaccination (40) and persist as a major subset more than 40 weeks after vaccination (38).…”
Section: Tb Vaccines Induce Polyfunctional T Cells In Animal Modelsmentioning
confidence: 99%
See 3 more Smart Citations